2017
DOI: 10.1073/pnas.1621447114
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons induced by endogenous or exogenous viral infections promote metastasis and relapse of leishmaniasis

Abstract: The presence of the endogenous Leishmania RNA virus 1 (LRV1) replicating stably within some parasite species has been associated with the development of more severe forms of leishmaniasis and relapses after drug treatment in humans. Here, we show that the disease-exacerbatory role of LRV1 relies on type I IFN (type I IFNs) production by macrophages and signaling in vivo. Moreover, infecting mice with the LRV1-cured Leishmania guyanensis (LgyLRV1 − ) strain of parasites followed by type I IFN treatment increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 61 publications
4
103
1
2
Order By: Relevance
“…It would be interesting to investigate whether the NE-induced IFN-b requirement for intracellular growth is a common trait for other L. donovani strains, including the reference strain in which the ISP2 gene is truncated. Recently, a role for IFN-b in promoting metastatic spread of L. guyanensis and relapse of infection was reported, associating antiviral responses to disease sustenance and severity (41). It is tempting to speculate that production of IFN-b is a common trait between Leishmania sp.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to investigate whether the NE-induced IFN-b requirement for intracellular growth is a common trait for other L. donovani strains, including the reference strain in which the ISP2 gene is truncated. Recently, a role for IFN-b in promoting metastatic spread of L. guyanensis and relapse of infection was reported, associating antiviral responses to disease sustenance and severity (41). It is tempting to speculate that production of IFN-b is a common trait between Leishmania sp.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of mRNA isolated from peripheral blood mononuclear cells (PBMCs) from VL patients before and after drug treatment, and ECs showed increased IFNA1, IFNB1, IFNAR1, and IFNAR2 transcripts in VL patient cells before drug treatment relative to post-treatment and EC samples (Figures 2A and 2B). Furthermore, expression of IFNA1 and IFNB1 was highest in CD1c + DCs relative to B cells (CD19 + ) and monocytes (CD14 + ) ( Figure 2C), other likely cellular sources of these cytokines in experimental leishmaniasis (Rossi et al, 2017; Silva-Barrios (C) The type I interferon (IFN) signaling pathway was identified as a canonical pathway (Z score of 2.828, p = 1.38 3 10 À4 ) in CD4 + T cells from VL patients by Ingenuity Pathways Analysis. The pathway visualization shows upregulated (red) and downregulated (green) genes within the dataset, relative to CD4 + T cells (legend continued on next page) et al, 2016).…”
Section: Type I Ifns Are Important Upstream Regulators Of Cd4 + T Celmentioning
confidence: 97%
“…A notable difference is that LRV is an endogenous viral element of the parasite itself while LDV is an exogenous mouse-specific virus that is co-hosted in Plasmodium-parasitized blood. Nevertheless, it was observed that the aggravation and metastasis of Leishmania lesions were not exclusively associated with LRV and that they could also be enhanced by co-infection with exogenous viruses 76 .…”
Section: Discussionmentioning
confidence: 99%